Ekowisata di Kawasan Cagar Budaya - Fajra Farhan Ekadj; Mahawan Karuniasa (EnviroScienteae, 2022)
This research takes a case study in a cultural heritage tourism area on Onrust Archaeological Park by taking into account the role of local communities. Tourism is an important sector in increasing the economic growth of a country or region. This study aims to improve the welfare of local communities by prioritizing ecotourism aspects. The researcher used a qualitative descriptive analysis approach with data collection in the form of document studies, observations, and semi-structured interviews. This approach is considered appropriate in analyzing, describing, and summarizing the conditions of tourism and the people who work on the Onrust Archaeological Park. In this study, the researcher found that the welfare of the working community can be influenced by 2 reasons, namely, the number of tourists and the availability of contract workers. Ecotourism is believed to be an alternative way to increase the number of tourists and the income of the people working on Onrust Archaeological Park.